Associations between night-time sleep duration and fasting glucose and ratio of triglyceride to high-density lipoprotein cholesterol among adults free of type 2 diabetes or without diagnosed type 2 diabetes: a multicentre, cross-sectional study in China - Rong Zhang; Li Zhang; Qiang Li; Minying Zhang; Feng Liu; Shuo Chen; Yu-Jie Niu; Xin Qi; Chunjun Li; Jiangshan He; Chenglin Hong; Yuxue Wang; et al. (BMJ Open)
Objectives We aimed to assess the associations between night-time sleep duration and fasting glucose (FG), triglyceride (TG) to high-density lipoprotein cholesterol (HDL-C) ratio and body mass index (BMI) among adults free of type 2 diabetes (T2D) or without diagnosed T2D.Design Cross-sectional study.Setting Medical examination centres at six hospitals in Beijing-Tianjin-Hebei region, China.Participants Participants were recruited via multistage, stratified cluster sampling. We included adults free of T2D or without diagnosed T2D who attended for physical examination and completed the validated questionnaire. 32 497 participants were included in the study, of whom 52.50% were men.Primary and secondary outcome measures FG, TG, HDL-C, height and weight were measured.Results Overall, 12.80% and 9.67% reported night sleep duration <7 hours and ≥9 hours, respectively; 6.91% had elevated FG and 3.57% had undiagnosed T2D. Sleep duration had an independent, U-shaped associated with FG (β1 (linear term)=−0.111, p=0.047; β2 (quadratic term)=0.008, p=0.026) with 6.9 hours of sleep associated with the lowest FG and a negative association with BMI (β=−0.154, p<0.001). BMI mediated a U-shaped association of sleep duration with TG/HDL-C (β1=−0.040, p=0.017; β2=0.003, p=0.023).Conclusions Both short and long night-time sleep was associated with elevated FG, and short sleep duration was associated with increased BMI. BMI mediated a U-shaped association between sleep duration and TG/HDL-C.